دراسة تأثير هجوم حجب الخدمة الموزع على شبكة العربات المتنقلة داخل المدينة - بشرى معلا (Tishreen University, 2016)
Distributed Denial of Service attack (DDOS) on Vehicular Ad Hoc Networks (VANETs) is considered to be one of the most serious types of attacks that can be targeted to those networks. The danger of this attack is in the difficulty of detection because of the cooperation of several attacking nodes in the network, and its impact on the availability requirement that is one of the most important security requirements in a network offering real-time applications .In our research, we study the effect of this attack on VANET network in the city, taking into consideration two cases. In the first case the target of the attack is the nodes, while in the second one, the target is the road side units (RSU). Simulation results have shown that this attack has a significant impact on both cases, by comparing the basic parameters of the network, such as throughput in/out and the number of dropped packets, before and after the attack. يعد هجوم حجب الخدمة الموزع على شبكات العربات المتنقلة من أخطر أنواع الهجومات التي يمكن أن تستهدف هذه الشبكات. تكمن خطورة هذا الهجوم في صعوبة اكتشافه كونه ينفذ من خلال التعاون بين أكثر من عقدة مهاجمة ضمن الشبكة، وبسبب تأثيره على استمرار الخدمة التي تقدمها الشبكة، أي انتهاك متطلب التوافرية الذي يعد من أهم متطلبات الأمن المطلوب تحقيقه في شبكة تقدم خدمة في الزمن الحقيقي. يهدف بحثنا إلى دراسة تأثير هذا الهجوم على شبكة عربات متنقلة تعمل داخل المدينة، آخذين بالحسبان حالتين، الأولى عندما يكون الهجوم موجهاً ضد عقد الشبكة والثانية عندما يكون موجهاً ضد الوحدات الجانبية على الطريق (RSU). وقد أظهرت نتائج المحاكاة التأثير الكبير لهذا الهجوم في كلتا الحالتين، وذلك من خلال مقارنة البارامترات الأساسية في الشبكة، مثل نفاذية الدخل/الخرج وعدد الرزم المسقطة, قبل الهجوم وبعده.